Graphene Particles Interfere with Pro‐Inflammatory Polarization of Human Macrophages: Functional and Electrophysiological Evidence (Adv. Biology 11/2021). Issue 11 (10th November 2021) - Povo‐Retana, Adrián; Mojena, Marina; Boscá, Alberto; Pedrós, Jorge; Peraza, Diego Alberto; Valenzuela, Carmen; Laparra, José Moisés; Calle, Fernando; Boscá, Lisardo
Abstract : Human Macrophages Polarization In article 2100882, Calle, Boscá, and co‐workers study the human macrophages tracking in the presence of 50 µg/ml of XG300 graphene particles (XG Sciences ref. xGnP C‐300; average size after fragmentation: 1–10 µm). The cell movements are recorded in an inverted light‐transmitted Z1 Cell Observer microscope (Zeiss) and monitored for 24 hours every 5 minutes by TrackMate plug‐in (Image J analysis software).